ARE SCHOOL CHILDREN READY TO DONATE BLOOD? - Thaver, Danyal Hasan; Masud, Nazish; Ashraf, Mariam (Journal of Ayub Medical College Abbottabad, 2014)
Background: Voluntary non-remunerated blood donors are considered the best among all different types of blood donors for improving the supply of safe blood. Though safe blood transfusion services have improved in Pakistan, but efforts are still required to optimize blood banks and improve recruitment of voluntary donors, such as senior school/college going students as a source of safe blood. This study looks into the awareness of senior school children concerning blood related issues including blood donation. Methods: This cross-sectional descriptive study enrolled 106 senior school students of private schools. Data were collected through self-administered questionnaire. Results: Although 90% of the students considered blood as an important entity for saving lives still 56.8% had never thought of donating blood. Respondents had good knowledge regarding the possible spread of HIV/AIDS, and Hepatitis B and C through unsafe transfusions. Possible hindrances to donating blood included fear of needles, fear of acquiring disease, lack of knowledge regarding where to donate blood and lack of trust on blood banks. More than half of the students believed that blood should be bought from professional blood donors. Conclusions: Senior school going children are not ready to donate blood. Lack of knowledge and prevailing misconceptions regarding blood transfusions need to be addressed and mechanisms to motivate and mobilize youth for becoming voluntary blood donors need to be established. Keywords: Blood transfusion, blood donation, blood donors